2014
DOI: 10.1007/s40069-013-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Resistant Mechanism into Base Components: Beam Action and Arch Action in Shear-Critical RC Members

Abstract: In the present paper, a behavioral model is proposed for study of the individual contributions to shear capacity in shearcritical reinforced concrete members. On the basis of the relationship between shear and bending moment (V = dM/dx) in beams subjected to combined shear and moment loads, the shear resistant mechanism is explicitly decoupled into the base componentsbeam action and arch action. Then the overall behavior of a beam is explained in terms of the combination of these two base components. The gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Center-to-center dimensions were used to define beam and column lengths and joint shear deformations were ignored because separate studies carried out by the authors indicated that the overall displacement responses were not influenced by incorporating special joint elements for the moment frame configurations considered in this study whose behavior is controlled by flexure. Considering joint deformations will be important for the case of shear-critical members (Jeong and Kim 2014).…”
Section: Prototype Model Materials and Elementsmentioning
confidence: 99%
“…Center-to-center dimensions were used to define beam and column lengths and joint shear deformations were ignored because separate studies carried out by the authors indicated that the overall displacement responses were not influenced by incorporating special joint elements for the moment frame configurations considered in this study whose behavior is controlled by flexure. Considering joint deformations will be important for the case of shear-critical members (Jeong and Kim 2014).…”
Section: Prototype Model Materials and Elementsmentioning
confidence: 99%
“…Another family of theoretical models relates concrete shear strength to the strain in the longitudinal reinforcement through various hypotheses regarding the crack location, orientation and the state of strain or stress (Zararis and Papadakis 2001;Tureyen and Frosch 2003;Park et al 2006;Jeong and Kim 2014). Recently, Shuraim (2014) introduced an approach, which relates the shear strength capacity or shear resistance in a concrete beam with the internal shear resulting from applied load, thus termed as shear demand.…”
Section: Initial Concrete Compressive Strain Ementioning
confidence: 99%
“…Although a number of researches have been conducted to evaluate shear strength of reinforced concrete beams for the last century, it is still hard to well predict actual shear strength because shear behavior of reinforced concrete beams is very complicating due to many parameters such as concrete compressive strength, stirrup ratio, shear span-todepth ratio, longitudinal reinforcement ratio, and so on Lee et al 2010;Labib et al 2013;Russo et al 2013;Mofidi and Chaallal 2014;Jeong and Kim 2014;Chiu et al 2016;El-Sayed and Shuraim 2016). On evaluating shear strength of reinforced concrete beams, even shear design provisions around the world are much different through each other, even from theoretical basis, specifically for reinforced concrete beams with stirrups (Eurocode 2 2004;ACI 318 2014;CSA A23.3 2014).…”
Section: Introductionmentioning
confidence: 99%